2004
DOI: 10.1161/01.cir.0000150400.15354.7d
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Transforming Growth Factor Antibody at Low but Not High Doses Limits Cyclosporine-Mediated Nephrotoxicity Without Altering Rat Cardiac Allograft Survival

Abstract: Background-Long-term treatment of cardiac transplant recipients with cyclosporine results in a progressive decline in kidney function in a large number of patients. This complication is one of the most important prognostic parameters that determine the outcome of cardiac transplantation. Transforming growth factor-␤ (TGF-␤) is one of the most potent mediators of the fibrogenic effects of cyclosporine. Methods and Results-With the use of an experimental rodent model, heterotopic heart transplantation was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…These observations were in agreement with Kang et al (2001). Li et al (2003) and Khanna et al (2004) detected tubular and vascular changes, including thickening of basement membranes and increased PAS staining of vascular structures in cyclosporine-treated animals. They added that afferent arteriolopathy was manifested by replacement of smooth muscle cells of afferent glomerular arteriole by a PAS-positive material.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These observations were in agreement with Kang et al (2001). Li et al (2003) and Khanna et al (2004) detected tubular and vascular changes, including thickening of basement membranes and increased PAS staining of vascular structures in cyclosporine-treated animals. They added that afferent arteriolopathy was manifested by replacement of smooth muscle cells of afferent glomerular arteriole by a PAS-positive material.…”
Section: Discussionsupporting
confidence: 87%
“…The renal damage induced by CsA is time and dose dependant (Khanna et al 2004). Curcumin was reported to be a regulator of the expression of inflammatory enzymes, cytokines, adhesion molecules, and cell survival proteins by modulating the activation of various transcription factors (Goel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the first series, allograft recipients were treated with CsA to show that caspase 3 activation was due to alloimmune activation. We previously showed that cardiac allografts survived to at least 117 days when given continuously at this dose (10) and that the increase in IFN-␥ and CD3 mRNA in a mixed splenocyte culture was prevented in cells taken from CsA-treated rats at posttransplant day 6 and stimulated ex vivo without added CsA (24). The latter indicates that the dose used effectively blocks both cytokine gene expression and lymphocyte activation.…”
Section: Resultsmentioning
confidence: 84%
“…To further complicate matters, other data suggest that outcomes may depend on the degree of TGFantagonism. Thus, cyclosporine-induced heterotopic heart transplantation survival was reduced by higher doses of TGF-antibody, whereas a lower antibody concentration inhibited both cyclosporine-induced expression of fibrogenic molecules and renal toxicity (280).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 96%